Lokalitas Jawa Dalam Novel Hati Sinden Karya Dwi Rahyuningsih - Randa Anggarista (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2021)
This study used perspective sociology of literary to identify form of Javanese locality in the novel of Hati Sinden by Dwi Rahyuningsih. This type of research is qualitative research with descriptive analysis method. The data in this research are in the form of text like words, sentences, or discourse in accordance with the formulation of problem. The source of data in this study is novel of Hati Sinden by Dwi Rahyuningsih published by Diva Press in 2011. The instrumen in this research is the author who is oriented towards research on Javanese locality in the novel of Hati Sinden by Dwi Rahyuningsih. Data collection techniques in this research were carried out in two stages, namely reading and talking notes. The data analysis technique was carried out through there stages, namely classification, description, and data presentation. The results show that in the novel of Hati Sinden was found there are representations of Javanese locality at the first form, locality in the art system in the form of tembang and untup-untup. Second, locality in the language system is to use Javanese language as a means of interaction for Javanese society. Third, locality in the belief system by holding thanksgiving events (salvation) in various activities, such as kenduren wetonan, kenduren raja kaya, nyadran, and nadhar or nadzar. Fourth, locality in the livelihood system by cultivating agriculture as a source of the economy. Fifth, locality in equipment and technology systems using lumpang kayu to pound various types of grains and vegetables.